Connotations of the “Adjective” and Its Structural Effects - AlMalki, Mohammed Abdullah (Al-Adab Journal, 2022)
The present research aimed at revealing the connotations given to the adjective by grammarians and tracing its structural effects: specification, clarification, veneration, praise, slander, mercifulness, detailing, generalization, and ambiguity. This research showed that the adjective in its entirety takes into account factors around the verbal speech like speaker’s and addressee’s conditions, discourse perspective, and the linguistic context. Also, the paper revealed the effects of the adjective on the linguistic structure by deducing the effects mentioned by grammarians in different references. This paper limited the effects of each of those connotations of the adjective to the linguistic structure. The effects mainly appeared in grammatical rules of the adjective and in some other grammatical functions, in the construction of the style, and in the multiplicity of its patterns.